NT-proBNP and Major Adverse Cardiovascular Events in Patients with ST-Segment Elevation Myocardial Infarction Who Received Primary Percutaneous Coronary Intervention: A Prospective Cohort Study - Zuoan Qin; Yaoyao Du; Quan Zhou; Xuelin Lu; Li Luo; Zhixiang Zhang; Ning Guo; Liangqing Ge (Cardiology Research and Practice)
Background. The prognostic significance of the amino-terminal fragment of the prohormone brain-type natriuretic peptide (NT-proBNP) in patients with ST-segment elevation myocardial infarction (STEMI) after percutaneous coronary intervention (PCI) has not been fully elucidated. Major adverse cardiovascular events (MACEs) are clinically viable indicators for the accurate, rapid, and safe evaluation of patients with STEMI. This study was designed to investigate the relationship between NT-proBNP levels and the occurrence of short-term MACEs in patients with STEMI who underwent emergency PCI. Methods. This prospective cohort study included 405 patients with STEMI aged 20–90 years who underwent emergency PCI at the First People’s Hospital of Changde City from April 6, 2017, to May 31, 2019. Stent thrombosis, reinfarction, congestive heart failure, unstable angina, and cardiac death were considered as MACEs in this study. The target-independent and -dependent variables were NT-proBNP at baseline and MACE, respectively. Results. There were 28.25% of MACEs. Age, number of implanted stents, Killip class, infarction-related artery, applied intra-aortic balloon pump (IABP), creatine kinase (CK) peak value, CK-MB peak value, TnI peak value, and ST-segment resolution were independently associated with MACE (P<0.05). In a multivariate model, after adjusting all potential covariates, Log2 NT-proBNP levels remained significantly associated with MACE, with an inflection point of 11.66. The effect sizes and confidence intervals of the left and right sides of the inflection point were 1.07 and 0.84–1.36 (P=0.5730) and 3.47 and 2.06–5.85 (P<0.0001), respectively. Conclusions. In patients with STEMI who underwent PCI, Log2 NT-proBNP was positively correlated with MACE within 1 month when the Log2 NT-proBNP was >11.66 (NT-proBNP >3.236 pg/mL).